Coronavirus shows how UK must act quickly before being shut out of Europe's health protection systems. (31st January 2020) - Flear, Mark; de Ruijter, Anniek; McKee, Martin
Abstract : The threat posed by 2019-nCoV and the fragmentation of existing health protection systems caused by Brexit call for urgent assessment of cross Europe cooperation, say Mark Flear, Anniek de Ruijter, and Martin McKee